On the Fluidic Forces and Shape Optimizations of Resonant Curved Cantilever Wings - Goussev, Andrey (My University, 2019)
Artificial flight on millimeter size scales has been a major challenge due to the difficulty in making a feasible flight mechanism in terms of fabrication, thrust and power used. Many have tried to copy animal flight but there has been little success at such sizes. One proposed solution is to make small thrusters out of resonant curved cantilevers which act as wings that follow a simple 1 degree-of-freedom motion. Such wings are free of joint friction, can be planarly fabricated using well documented techniques, can be predictably scaled to different sizes, and have been shown to generate a net thrust. In this thesis, the work investigates the nature of the wings’ thrust through thorough studies of computational fluid dynamic simulations to understand how they interact with the surrounding fluid and how exactly the forces are generated. Specifically, it considers the role of unsteady lagged fluid waves generated by the wings and explains how the wing-fluid interactions relate to drag coefficients at low to high flapping amplitudes and Reynolds numbers ranging from 100 - 100 000. It then studies the effect of different wing aspect ratios on the net force and power efficiencies. The results are then extended to a general dependence on the wings’ aspect ratio which allows for this parameter to be used in optimizing the wings’ net force/power used. Test wings are then made using an updated fabrication method and Molybdenum as the curve-inducing material in an attempt to produce more environmentally-stable wings with important successes, failures and improvements discussed. Results show that such Molybdenum-based wings are practical for flight, and that resonant curved cantilevers wings can be made more feasible by simple changes to their shape.
Keywords: Fluid Dynamics; MEMS; MAVS; RESONANCE; FLIGHT